Sosialisasi Dampak Profesi Akuntansi pada Era Digital 5.0 - Giovanny Kristianto; Lusi Yuliarti; RR Farida Istiningrum (Pusat Riset dan Inovasi Nasional, 2024)
The Digital Era 5.0 brings significant changes in various aspects of life, including the accounting profession. Advanced technologies such as artificial intelligence (AI), blockchain, and big data analytics are changing the way accountants work. The community service activities carried out at SMK Swagaya 2 Purwokerto aim so that when they graduate from SMK they can take higher education to get a better job in the future. The challenge for accountants in the future is that if they do not follow technological changes, they will be replaced by computers, so that the job market will be increasingly difficult. In this community service, based on research conducted by previous researchers, it shows that digital technology offers significant opportunities and challenges for accountants, and proper socialization is very important to maximize the benefits of this technology. The enthusiasm of the participants can show that there is motivation in each of them to want to progress and develop and will not go hand in hand with the increasingly developing 5.0 technology.